A Comparison Of Multiple Linear Regression And Single Exponential Smoothing For Predicting Rice Production In North Aceh - Cindy Anindia Putri; Angga Pratama; Zalfie Ardian (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
North Aceh Regency is the largest rice producer in Aceh Province; however, rice production has fluctuated and shown a downward trend from 2019 to 2023. This study aims to analyze the factors influencing rice production and to compare the Multiple Linear Regression and Single Exponential Smoothing (SES) methods in predicting rice production in North Aceh Regency. The variables used include harvested area, productivity, rainfall, and flooding. The Multiple Linear Regression method was used to analyze the relationships among variables, while SES was used to make predictions based on historical data. The analysis results indicate that productivity has the greatest influence on rice production, followed by harvested area. Rainfall and flooding also affect production, but their influence is relatively small. Model evaluation shows that Multiple Linear Regression has an MSE of 2156056.09, a MAD of 627, and a MAPE of 9.04%, which is better than Single Exponential Smoothing with an MSE of 51,613,195, a MAD of 3,867, and a MAPE of 28.57%. Based on these results, the Multiple Linear Regression method has a higher level of accuracy in predicting rice production in North Aceh.